PHILOSOPHICAL WORLDVIEWS ON THE NATURE OF THINKING AND ACTING - Baca, Ferit (European Scientific Journal, ESJ, 2014)
“There is nothing unchangeable in the world, Only variability is unchangeable.” Albert Einstein According to ancient Greek philosophers, philosophy is the loveofwisdom that hoists human consciousness, where, through reason, meanings of unknowns are distinguished and attested. The science of philosophy realizes the general recognition of the world’s existence. As an early science in critical thinking, itdeveloped the progressive performance of intellectual knowledge in man, by summarizing a set of unified principles about recognition, where through the reason dictates the concepts on society and nature as a change and overall knowledge of the world and nature laws. Philosophers consider the opinion as an intellectual property that helps us find answers and solutions to the important questions ad problemssuch as: "If you are not a man who thinks, then what kind of man are you?", or "Are we what we think?". Thinking is characterized not only by the study of visible objects as symbols, but also by the treatment of hypotheses for the acquisition of more accurate knowledge of various scientific disciplines. It was Plato, who unveiled the thought as a special feature of the thinkers who brought the necessary changes in society. While Descartes declared that he doubted everything, butonly for one thing, - he said, - I do not doubt: That I think! The thought that arises and emanates from the self is the origin of the goals and the vision about the surroundinguniverse. It is a reference to the mind, which is based on experience, on the meaning of things and on the manner how we perceive phenomena and occurrences of society and nature. Thus, human activity is directly associated with his thoughts embedded in the psyche and experienced until the transformation of them intomentalities and habits, under which it operates. The path described up to present days, but also the one expected to be described tomorrow is the product of the ideas of human society.